Students’ Perception towards English Teacher’s Interpersonal Communication Skill - Nirmalasari M. Malaimakuni (Intelektual Pustaka Media Utama, 2016)
The students’ perceptions to their teacher’ interpersonal communication skill at Junior High School (SMP N 3 Kupang). This study aims at knowing: 1) the teacher’s interpersonal communication skill perceived students; 2) the difference of male and female students’ perception to their teacher’s interpersonal communication skill. The research uses descriptive quantitative method. The research subjects of this study are 27 male and 27 female students which are choosen randomly with precision 16% out of 178 for female students and 15% out of 185 male students. The result shows that the teacher’ interpersonal communication skill which includes openness, empathy, supportiveness, positiveness, and equality. The male students perceived their teacher’s interpersonal communication skill in which equality is as highest position at score with 18.51% usually, then positiveness at 17.90%, followed by supportiveness at 15.34% and empathy at 15.27%, and the lowest position is openness at 14.19%. Meanwhile, female students have perception, such as; empathy takes place in the highest position at 17.12% on usually performance of teacher’s interpersonal communication skill compared with supportiveness, positiveness, openness, and equality (16.40%, 14.81%, 13.27%, and 12.16%, respectively). Then, on sometimes perception, female students perceived that supportiveness is the highest score with 53.96%. Then followed by equality with 51.85%, empathy with 50.46%, openness with 49.69% and the lowest score is positiveness with 42.59%. Meanwhile, seldom perception is on the level of 42.59% at positiveness, 37.03% at openness, 35.97% at equality, 32.40% at empathy, and supportiveness at 29.62%.